PHILOSOPHY OF SCIENCE AND INFORMATION SYSTEMS: FOUNDATIONS AND PRACTICAL CHALLENGES - Aditya Lapu Kalua; Yampi R Kaesmetan; Syafiul Muzid; Hasanudin Jayawardana; Harfebi Fryonanda; Mochammad Agung Wibowo (Yayasan Nuraini Ibrahim Mandiri, 2026)
The philosophy of science has evolved from ancient times to the present day. Even today’s advancements in information technology are inextricably linked to the philosophy of science. Information systems are a key component of these technological advancements. They have evolved from mere technical tools for managing data into socially constructed entities rich in meaning that influence various aspects of society. This demonstrates that information systems cannot be separated from the social, cultural, and ethical contexts that surround them. The connection between the philosophy of science and information systems has become increasingly significant with the advent of AI technology. The philosophy of science has three main pillars—ontology, epistemology, and axiology—which serve as its conceptual and methodological foundations. Ontology provides a framework for representing reality that serves as the foundation for system modeling; epistemology guides research paradigms and the methodologies used to acquire and validate knowledge; while axiology emphasizes the importance of values and ethics in both the design and implementation of information systems. With the development of technology, information systems are no longer viewed merely as technical devices, but rather as social constructs with far-reaching impacts. This transformation has become increasingly evident in the era of AI, making the philosophy of science a critical instrument that guides technological innovation to remain aligned with human values and broader social goals.